2017
DOI: 10.1155/2017/4832051
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Risk Factors for Postoperative Infectious Complications after Percutaneous Nephrolithotomy

Abstract: This study was to evaluate the risk factors of infectious complications after percutaneous nephrolithotomy (PCNL) and build a prediction tool for postoperative complications based on the risk factors. A total of 110 male (67.1%) and 54 female (32.9%) patients who underwent PCNL for renal stones between 2010 and 2014 in our institute were included. A detailed clinical information and laboratory results were obtained from patients. Systemic inflammatory response syndrome (SIRS) and postoperative fever were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 19 publications
5
27
0
1
Order By: Relevance
“…In this study 28.9% developed SIRS in post-operative period. Similar results were seen in other studies 1,8,[10][11] while in the study in the Department of Urology of Mayo Clinic, it was observed in only 9% of patients. 5 Sepsis was seen in 6.2 % of patients which was similar to other results 4,[11][12] while Mayo clinic study showed low sepsis rates which was as low as 0.9 % .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study 28.9% developed SIRS in post-operative period. Similar results were seen in other studies 1,8,[10][11] while in the study in the Department of Urology of Mayo Clinic, it was observed in only 9% of patients. 5 Sepsis was seen in 6.2 % of patients which was similar to other results 4,[11][12] while Mayo clinic study showed low sepsis rates which was as low as 0.9 % .…”
Section: Discussionsupporting
confidence: 90%
“…11,13 The study conducted at Fudan University, China concluded stone size and abnormal urinalysis to be significantly associated with SIRS. 1 A Thai study found that preoperative urine culture, pelvic urine culture and stone culture were positively associated with post operative SIRS. 8 However, a Dutch study showed no relation between preoperative urine culture with post operative fever or SIRS.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al, in their study on patient undergoing percutaneous nephrolithotomy (PCNL), observed that preoperative urine white blood corpuscles count and stone size were risk factors for both fever and systemic inflammatory response syndrome (SIRS). (20) Even though fever may cause diagnostic confusion (central fever vs infectious), maintenance of normothermia appears to be desirable therapeutic goal in managing patients with damaged or at-risk brain tissue. (21) Laboratory evidence is quite clear regarding the adverse effects of fever in terms not only of functional outcomes, but also histological and neurochemical injury in these cases.…”
Section: Causesmentioning
confidence: 99%
“…Инфекционно-воспалительные осложнения удлиняют сроки пребывания пациентов в стационаре и последующий реабилитационный период, увеличивают расходы на лечение. К наиболее распространенным послеоперационным осложнениям ЧПНЛТ наряду с пиелонефритом и проблемами, вызванными резидуальными камнями, относят фебрильную лихорадку (до 32,1 % случаев) [5].…”
unclassified